KARAKTERISTIK SENSORI VIRGIN COCONUT OIL (VCO) YANG DIEKSTRAKSI MENGGUNAKAN EKSTRAK KULIT BUAH NANAS DENGAN KOMBINASI RAGI ROTI DAN RAGI TEMPE - Rizki Rentisia Mukti; Usman Pato; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This study aims toget the best treatment of the use crude bromelain from peel pineapple extract with combination baker yeast and tempeh mold. The research method used a completely randomized design with four treatments and four replications. The treatments used crude bromelain extract and 0.5 gram yeast and mold with variation treatment: RK1 (crude bromelain extract), RK2 (crude bromelain extract + baker yeast 0.375% and tempeh mold 0.125%), RK3 (crude bromelain extract + baker yeast 0.25% and tempeh mold 0.25%), RK4 (crude bromelain extract + baker yeast 0.125% and tempeh mold 0.375%). The data obtained were statistically analyzed using analysis of variance and continued with Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results showed that the combination of baker yeast and tempeh mold not significantly affected descriptive sensory test of color and flavour. Based on the result of this research, the combination of crude bromelain extract + baker yeast 0.375% and tempeh mold 0.125% was chosen as the best treatments. Virgin Coconut Oil (VCO) from this treatment had a clear color and had distinctive aroma of coconut oil. Keywords: bromelain, baker yeast,tempeh mold, virgin coconut oil (VCO)